CONSTRUCTION OF COSPECTRAL K-UNIFORM HYPERGRAPH - Pradananta, Galih
This final project deals with hypermatrix as a generalization of matrix. Family of hypermatrices conserves to be vector space just like in matrix. Adjacency hypermatrix is defined to be substitution of adjacency matrix for a hypergraph. Then hyperdeterminant is defined from adjacency hypermatrix. Finally from it, polynomial characteristic is defined. Properties of hypermatrix and hyperdeterminant have been studied in this final project, of course, and also in many references. They give us knowledge about hypergraph cospectrality. From that can be determined a hypergrapgh is cospectral with other hypergraph or a hypergraph is determined by its spectrum. The main result of this final project is the construction of cospectral k-uniform hypergraph that is not isomorphic. Some k-uniform hypergraphs that determined by its spectrum are mentioned in this final project. Cospectral hypergraph within this final project is restricted to particular k-uniform hypergraph.